Intellectual capital disclosure: the Portuguese case - Martins, M. M.; Morais, A. I.; Isidro, H.; Laureano, R. M. S. (Journal of the Knowledge Economy, 2018)
The purpose of this research is to identify the factors that can explain practices of voluntary disclosure of information on intellectual capital (IC). This is an empirical quantitative study that seeks to examine the influence of certain firm characteristics (firm size, auditor type, ownership concentration, industry, proportion of non-executive directors (NEDs) on the board, chairman/CEO duality and audit committee) on intellectual capital disclosure (ICD) in Portuguese companies. ICD data for this longitudinal study were gathered from the annual reports of 32 Portuguese listed firms over 5 years using content analysis. The results of this study indicate that firm size and industry are explanatory factors of the level of disclosure of information on intellectual capital. One of the limitations of the empirical part of the study derives from choosing the content analysis method because it is subject to the subjectivity of interpretation. Another limitation is the small sample size and the application only to Portugal which reduces the ability to generalize the results to other settings. This study contributes to the IC literature, providing new empirical data covering the analysis of 5 years of disclosure related to corporate governance.